An ontology-based context aware system for Selective Dissemination of Information in a digital library - Martínez, Juan Pablo (2010)
Users of Institutional Repositories and Digital Libraries are known by their needs for very specific information about one or more subjects. To characterize users profiles and offer them new documents and resources is one of the main challenges of today's libraries. In this paper, a Selective Dissemination of Information service is described, which proposes an Ontology-based Context Aware system for identifying user's context (research subjects, work team, areas of interest). This system enables librarians to broaden users profiles beyond the information that users have introduced by hand (such as institution, age and language). The system requires a context retrieval layer to capture user information and behavior, and an inference engine to support context inference from many information sources (selected documents and users' queries).